Analisis Material Requirement Planning dengan Lot Sizing pada Produk Asam Sulfat di PT. Petrokimia Gresik - Tarigan, Feby Yola Br; Nugraha, Isna (Fakultas Teknik Universitas Tulang Bawang, 2025)
In the industrial world, material requirements planning is a very important foundation for smooth operations and business success so that production disruptions and increased costs can be avoided. PT. Petrokimia Gresik is the most complete fertilizer producer in Indonesia, one of which produces sulfuric acid. The problems experienced by PT. Petrokimia Gresik Produksi IIIA, namely Sulfuric Acid production, has been temporarily stopped due to excess product stock in the distribution line. Therefore, the aim of this research is to carry out product inventory planning by determining the quantity and when orders can be placed so that over stock and inventory costs can be minimized. To solve this problem, the Material Requirement Planning method is used using the lotting technique. Based on the research results, it was found that the MRP method should be applied in companies with lot sizing Economic Order Quantity because it has the smallest total ordering and inventory costs. It was found that the total order for sulfuric acid using the economic order quantity was 1,390,000 tons, which resulted in a difference of 54,534.06 tons of sulfuric acid from the company's total orders and by applying the economic order quantity the company would save inventory costs of IDR 3,697,073,366.00. Keywords: Economic Order Quantity, Least Total Cost, Lot For Lot, Material Requirement Planning, Supply